Down-regulation of autophagy proteins is associated with higher mTOR expression in the placenta of pregnant women with preeclampsia - Weel, I. C. [UNESP]; Ribeiro, V. R. [UNESP]; Romão-Veiga, M. [UNESP]; Fioratti, E. G. [UNESP]; Peraçoli, J. C. [UNESP]; Peraçoli, M. T.S. [UNESP] (FapUNIFESP (SciELO), 2022)
Autophagy is a lysosomal degradation pathway that removes protein aggregates and damaged organelles maintaining cellular integrity. It seems to be essential for cell survival during stress, starvation, hypoxia, and consequently to the placenta implantation and development. Preeclampsia (PE) is a multisystemic disorder characterized by the onset of hypertension associated or not with proteinuria and other maternal complications. Considering that the placenta seems to play an important role in the pathogenesis of PE, the objective of the present study was to evaluate protein levels of light chain protein (LC3), beclin-1, and the mammalian target of rapamycin (mTOR) in the placenta of pregnant women with PE. Placental tissues collected from 20 women with PE and 20 normotensive (NT) pregnant women were evaluated for LC3, beclin-1, and mTOR expression by qPCR and immunohistochemistry. The mRNA for LC3 and beclin-1 were significantly lower, while mTOR gene expression was significantly higher in the placenta of pregnant women with PE than in the NT group. Placentas of PE women showed significantly decreased protein expression of LC3-II and beclin-1, whereas mTOR was significantly increased compared with the NT pregnant women. There was a negative correlation between protein expression of mTOR and LC3-II in the placental tissue of PE women. In conclusion, the results showed autophagy deficiency suggesting that failure in this degradation process may contribute to the pathogenesis of PE; however, new studies involving cross-talk between autophagy and inflammatory molecular mechanisms might help to better understand the autophagy process in this obstetric pathology.
Keywords: Autophagy; Beclin-1; LC3; mTOR; Placenta; Preeclampsia